Investigation on the processability, structure and properties of micro-/nano-fiber composite yarns produced by trans-scale spinning. Issue 3 (June 2022) - Yang, Yuchen; Quan, Zhenzhen; Zhang, Hongnan; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
While the conventional composite yarns are generally confined to micro-scale fibers, composite yarns of micro-/nano-fibers have been fabricated by integrating carded fibrous web with electospun nanofibers, namely trans-scale spinning proposed in our latest works. In the micro-/nano-fiber composite yarns, the nanofibers with low content were embedded uniformly both inside and outside with short fibrous segments, which endows themselves with superior functionality without altering the intrinsic comfort, such as the durably efficient antibacterial capability of comfortable cotton fabric. In the present work, universal applicability of the trans-scale spinning approach has been investigated systematically. Various composite yarns were successfully fabricated by the novel spinning technique. The effects of three critical factors, microfiber materials, nanofiber polymers and spinning methods, on the structural characteristics and physical properties of composite yarns were demonstrated experimentally and theoretically. It was indicated that nanofibers are distributed uniformly in all resulting yarns, but broken segments of them in synthetic microfiber composite yarns are shorter than that in cotton composite yarns, which may result from different fiber appearance. Besides, the composite yarns present comparable physical properties (tensile performance, hairiness, unevenness) to those of pristine microfiber yarns, which enable themselves of being manufactured into all kinds of fabrics for industrial applications. The results reported in the current study would facilitate the design and preparation of composite yarn and the development of functional textiles.